PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KUALITAS PROSES DAN HASIL BELAJAR GEOGRAFI PESERTA DIDIK PADA MATERI INTERAKSI MANUSIA DAN LINGKUNGAN DALAM DINAMIKA HIDROSFER TAHUN AJARAN 2013/2014 (IMPLEMENTASI KURIKULUM 2013 DI KELAS X ICT I - Arizona, Neto Armando (Pendidikan Geografi, 2013)
PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KUALITAS PROSES DAN HASIL BELAJAR GEOGRAFI PESERTA DIDIK PADA MATERI INTERAKSI MANUSIA DAN LINGKUNGAN DALAM DINAMIKA HIDROSFER TAHUN AJARAN 2013/2014 (Implementasi Kurikulum 2013 di kelas X ICT IPA 2 SMAN 1 Karanganyar) NetoArmandoArizona 1*Danang Endarto, ST, M.Si2Singgih Prihadi, S.Pd, M.Pd2 1) Pendidikan GeografiFKIPUNS,2)Dosen pendidikan Geografi FKIP Universitas Sebelas Maret Surakarta*)Keperluan korespondensi, Hp : 085647553311, Email:Netoarmandoanu@gmail.com  ABSTRACT The purposes of this research are: 1)To improve the quality of the learning process of learners Project Based Learning in learning geography. 2)To improve the quality of learning outcomes of learners Project Based Learning in learning geography.Questionnaires, observation sheets, tests, documentation and interviews are used to collect the research data. The validity of the data is measured using the techniques of triangulation : triangulation method and triangulation observer. The data analysis techniques used are qualitative data analysis techniques and quantitative data analysis techniques.The results of this research indicate that based on the observation sheet, the average percentages of the learning process achievement in the classroom of each aspect are : The teamwork in the first cycle is 61.33% and 81.33% in the second cycle. The interest and enthusiasm of students in the first cycle is 65.33% and 88% in the second cycle. The motivation of learners on the first cycle is 69.33% and 80% in the second cycle. The test result of students in the first cycle is 48.4% over the KKM, while in the second cycle it is 87.1% over the KKM.  Keyword: Project Based Learning, the quality of procees and learning outcomes, curriculum 2013.